Coping strategies during legally enforced quarantine and their association to psychological distress level: a cross-sectional study. (August 2022) - Klee, L.; Fabrice, A.; Eisenburger, N.; Feddern, S.; Gabriel, C.; Kossow, A.; Niessen, J.; Schmidt, N.; Wiesmüller, G.A.; Grüne, B.; Joisten, C.; ,
Abstract: Objectives: The non-pharmacological measures to contain the COVID-19 pandemic may lead to considerable psychological distress. The aim of the CoCo-Fakt study was to investigate possible coping strategies and their effects on psychological distress during legally enforced quarantine of infected persons (IPs) and their close contacts (CPs). Study design: This was a cross-sectional cohort study. Methods: From 12 December 2020 to 6 January 2021, all IPs and their CPs (n = 8232) registered by the public health department (Cologne, Germany) were surveyed online. Psychosocial distress and coping were measured using sum scores; free-text answers related to specific strategies were subsequently categorised. Results: Psychosocial distress was higher in IPs than in CPs ( P < .001). Although the mean coping score did not differ between both groups, it was influenced by the reason for quarantine (IP vs CP) besides gender, age, socio-economic status, living situation, psychological distress, resilience, physical activity and eating behaviour. This final regression model explained 25.9% of the variance. Most participants used active coping strategies, such as contact with the social environment, a positive attitude and hobbies. Conclusions: Although psychological distress was higher in IPs than in CPs during the quarantine period, the mean coping score did not differ. The strategies most frequently used by IPs and CPs were activating social networks, a healthy lifestyle and professional support systems, such as the health department helpline. Appropriate advice should be implemented to prevent long-term psychological consequences when supporting affected people.